Maternal nutritional status and offspring childlessness: Evidence from the late-nineteenth to early-twentieth centuries in a group of Italian populations. (2nd September 2022) - Manfredini, Matteo; Breschi, Marco; Fornasin, Alessio; Esposito, Massimo
Abstract : The role of maternal nutrition in affecting offspring fertility, through alteration of foetal programming, has been demonstrated in animal-based experiments. However, results from human populations appear inconsistent and sometimes contradictory, likely because they have been based on single famine events. In this paper, we adopt a different approach. We combine official annual time series of daily nutrient availability with a sample of women's reproductive histories from the 1961 Italian Census to investigate the role of maternal nutritional status in pregnancy on offspring childlessness. The analysis therefore covers cohorts of females born between 1861 and 1939. Our results show a negative association between calorie availability in pregnancy and the odds of offspring childlessness, whereas no association is found between protein availability and offspring childlessness. The consequences of poor calorie intake were aggravated during the summer, likely due to the participation of pregnant women in physically demanding work.